Orchestrated Paradiplomacy: A Multilevel Governance Analysis of the Indonesia-China ‘Two Countries, Twin Parks’ Initiative - Riyanto, Budi; Keliat, Cyntia; Lamza, Widia (Journal of Paradiplomacy and City Networks, 2025)
This study examined the Indonesia-China ‘Two Countries, Twin Parks’ (TCTP) initiative as a novel form of economic paradiplomacy nested within the broader Belt and Road Initiative (BRI). TCTP transcends traditional sub-national diplomacy, representing a complex, multi-tiered arrangement of actors and interests. Unlike the autonomous “micro-diplomacy” of the post-Cold War era, the TCTP demonstrates how central states effectively mobilize sub-national intermediaries—specifically provincial governments and industrial estate operators—to achieve transnational strategic goals. This research extends Multilevel Governance (MLG) theory by conceptualizing “orchestrated paradiplomacy” as a distinct, nested form of sub-national diplomacy embedded within global geoeconomic strategies. This study argues that the new paradiplomacy framework is essential to deconstruct the intricate interplay of actors at the supranational, national, and sub-national levels. Using a qualitative method that analyzed official documents, academic literature, and credible reports, this study mapped TCTP’s architecture and actor motivations. The findings revealed that while the initiative has created significant economic opportunities through transnational supply chain integration, it has simultaneously also generated profound governance challenges. These challenges manifest as policy coordination gaps and the externalization of negative socio-environmental impacts at the local level, stemming from misaligned priorities between the geoeconomic objectives of higher governance tiers and the regulatory responsibilities of local authorities. The study concluded by discussing critical policy implications, arguing that a rebalancing of governance is required to empower local ecological and social oversight, thereby addressing the “governance deficit” inherent in state-orchestrated development models.